An Integrated Management Paradigm for Skull Base Chordoma Based on Clinical and Molecular Characteristics - Abdallah, Hussein M.; Gersey, Zachary C.; Muthiah, Nallammai; McDowell, Michael M.; Pearce, Thomas; Costacou, Tina; Snyderman, Carl H.; Wang, Eric W.; Gardner, Paul A.; Zenonos, Georgios A. (Journal of Neurological Surgery Part B: Skull Base, 2021)
Objective Previous work categorized skull base chordoma (SBC) into three genetic risk groups based on 1p36 and homozygous 9p21(p16) deletions, accounting for a wide variability in prognosis (A = low-risk, B = intermediate-risk, C = high-risk). However, it remains unclear how these groups could guide management.Study Design By integrating surgical outcome and adjuvant radiation (AdjXRT) information with genetic data on 152 tumors, we sought to develop an evidence-based management algorithm for SBC.Results Gross total resections (GTRs) were associated with improved progression free survival (PFS) in all genetic groups. For Group C tumors, GTR and AdjXRT independently contributed to PFS (multivariate Cox proportional hazard ratio [HR] = 0.14, p = 0.002, and HR = 0.40, p = 0.047, respectively). For Group B tumors, AdjXRT improved outcomes only when GTR was not feasible (log-rank p = 0.008), but not following GTR (log-rank p = 0.54). However, 24 of 25 Group A tumors underwent GTR, and AdjXRT for these did not confer any benefit (log-Rank p = 0.285). The high GTR rates in Group A could be explained by smaller tumor sizes (mean = 0.98cc/4.08cc/4.92cc for Group A/B/C, respectively, p = 0.031) and lack of invasiveness. Group A tumors were also more frequently diagnosed in young people (p = 0.002) as asymptomatic lesions (p = 0.001), suggesting that they could be precursors to tumors in higher risk groups.Conclusion Genotypic grouping by 1p36 and homozygous 9p21(p16) deletions can predict prognosis in SBC and guide management. GTR remains the cornerstone of SBC treatment and can be sufficient without AdjXRT in low and intermediate risk tumors. Low-risk tumors are associated with a less invasive phenotype, which makes them more amenable to GTR.
Keywords: chordoma; clival chordoma; skull base; genetics; fluorescent in situ hybridization; radiotherapy